2014
DOI: 10.1080/14635240.2014.915758
|View full text |Cite
|
Sign up to set email alerts
|

Training sports coaches to tackle tobacco: formative evaluation of the SmokeFree Sports campaign

Abstract: . G. Stratton@swansea.ac.uk (01792 606544) T. A. Hilland et al. 2 Smoking is one of the leading causes of preventable morbidity and death in England, and is an addiction largely taken up in youth. Given the need for early prevention strategies, this formative study evaluated sports coaches' perceptions of a preliminary SmokeFree Sports (SFS) campaign. The research was conducted in five youth clubs with eight coaches who attended a Level 1 Brief Intervention Training workshop. Semi-structured interviews… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…The present study has several strengths. First, in accordance with MRC guidance for the development of complex interventions, SFS was designed following extensive formative work, school and community feasibility studies [ 29 , 41 , 42 ]. Second, this study adopted a mixed-methodology approach consistency with the Standard Evaluation Framework for physical activity interventions [ 85 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The present study has several strengths. First, in accordance with MRC guidance for the development of complex interventions, SFS was designed following extensive formative work, school and community feasibility studies [ 29 , 41 , 42 ]. Second, this study adopted a mixed-methodology approach consistency with the Standard Evaluation Framework for physical activity interventions [ 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…The intervention was designed in accordance with the NICE guidance [ 35 ] and the Medical Research Council (MRC) framework for developing and evaluating complex interventions [ 40 ]. Phase one of SFS (February-June 2011) was a community feasibility trial in five youth clubs, which received 12 weeks of coaching activities (dance, dodge-ball and boxing) delivered by trained sports coaches [ 29 , 41 ]. A formative evaluation demonstrated that the intervention helped to prevent youth from initiating smoking and had positive benefits on their attitudes and knowledge about smoking [ 29 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recognising the impact of coach education on programme delivery is also important. Several studies have explored the efficacy of brief intervention training for coaches in various aspects of health promotion [50,51]. Previous studies of community-based PA interventions highlight that coach training should go beyond 'the typical' football and/or multi-sport qualifications in order to accommodate the increasing needs of programme participants [46].…”
Section: Fidelitymentioning
confidence: 99%
“…Coaches are also perceived to be proximate and positive role models for health behavior change [21]. There are examples of health prevention programs delivered by sport coaches [22][23][24], albeit not in the context of SFD and not specifically targeting action in vulnerable groups. In addition, the effectiveness of the interventions depend on the extent that coaches manage to deliver appropriate knowledge, install appropriate attitudes, and apply appropriate skills regarding the health promotion activities to be delivered [25]; which is especially challenging within SFD.…”
Section: Introductionmentioning
confidence: 99%